Web Based Digital Storytelling Competition Application - Mohamed, Ahmed Ali Othman (2010)
The main purpose of this study is to design online application for the digital storytelling competition for secondary school students and teachers. The prototype which developed and executed by PHP language for secondary school students and teachers were presented and tested by using methods and usability test in order to get know the percentage of the system acceptability. The application of the online technologies in this study allows the participants to compete and evaluate through web based competition.